PENGARUH BUERGER ALLEN EXERCISE TERHADAP KEKUATAN OTOT PADA PASIEN DIABETES MELLITUS TIPE 2 - Setyorini, Andri; Hartiningsih, Sri Nur; Martani, Eka Ayunda; Darmawan, Ardhian Indra (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2025)
Background: Diabetes mellitus has a side effect of decreasing neuropathy which can cause people to have less sensitive feet. Sensation or decreased sensitivity of the feet is one of the risk factors for ulcers. It is necessary to do Buerger Allen Exercise physical activity to increase muscle strength in patients with Type 2 Diabetes Mellitus. Research Objective: To determine the Effect of Buerger Allen Exercise on Muscle Strength in Patients with Type 2 Diabetes Mellitus. Research Method: This type of research is a pre-experiment with a one-group pre-post test design. The respondents in this study were patients with type 2 diabetes mellitus at the Pleret Bantul Yogyakarta Health Center. The population in this study was 32 patients with type 2 diabetes mellitus at the Pleret Public Health Center Bantul Yogyakarta. The sampling technique used was random sampling with a total of 20 respondents. This research was conducted in February 2025. The instrument used was Manual Muscle Testing. The test used was the Paired T-test, to measure the presence or absence of influence. Research Results: The average muscle strength before being given Buerger Allen Exercise was 73.65. The average muscle strength after being given Buerger Allen Exercise was 91.65. There was an increase in muscle strength score of 18.00. The p value of the Paired T-test = 0.000 (p value <0.05). Conclusion: There is an Effect of Buerger Allen Exercise on Muscle Strength in Type 2 Diabetes Mellitus Patients at the Pleret Bantul Health Center, Yogyakarta.